Pelatihan Pembuatan Pupuk Kompos Organik Limbah Rumah Tangga Pada Ibu-Ibu Pkk Rt 03 Rw 05 Kalurahan Mojo Kecamatan Pasar Kliwon Surakarta - Nur Rokhimah Hanik; Tri Wiharti; Rindi Diah Ayu Fitriani; Fiky Ariska Cahyani; Umi Salamah (Jurnal Gema Ngabdi, 2023)
Residents of RT. 03RW. 05 Mojo Village, Pasar Kliwon District, Surakarta, totaling 20 families. and the majority of the population work as entrepreneurs and casual laborers. Most of the PKK members' mothers (wives) are housewives. They really need additional financial income to meet family needs. They have never received counseling or training on making organic compost from universities or other institutions. From the results of interviews, several female PKK members wanted counseling and training in making organic compost fertilizer as an alternative to increase their income financially. For this reason, the Biology Education Study Program Abdimas Team will provide training to PKK RT 03 members on making organic compost from family waste. The objectives of this community service are 1. Provide training on how to make organic compost. 2. Provide training/skills in applying organic compost with planting media. The training was held 2 times. The method used is lectures and questions and answers, as well as practical guidance on how to make and apply organic compost. The target of this training is to increase understanding of how to make organic compost by 20%, and a skill score of >70. From the results of the training on making organic compost for women from PKK RT 03 RW 05, Mojo sub-district, it can be concluded that: There is an increase in understanding of the process of making organic compost from an average score of 38.23 to 89.14, meaning there is an increase in understanding of 51.25 ( 153.04%). For the skill scores for making compost and its application to media and plants, PKK members obtained scores of 88.92 and 88.71, which means that all participants are skilled in making fertilizer and applying it to plants.